PERLINDUNGAN HAK KONSTITUSIONAL BURUH - Wilma Silalahi (Legalita, 2019)
Indonesia as a democratic rule of law places the rights of citizens as part of the basic rights guaranteed and protected by the state. The rights of citizens are further regulated in the 1945 Constitution as the highest basic law, hereinafter referred to as constitutional rights. However, in its implementation there are still often violations of labor rights. Over time workers who feel their constitutional rights are impaired by the enactment of norms in the Manpower Act submit a judicial review to the Constitutional Court related to the conception of protecting labor rights. The writing of this article uses the normative legal research method. The conclusion of this article is that the concept of protection of labor rights in legislation that guarantees the constitutional rights of workers or workers' normative rights that can be broadly grouped into four, namely economic rights, political rights, rights that are medical nature, and social rights. Conception of Labor Rights Protection According to the Constitutional Court as reflected in Decision on Case Number 012 / PUU-I / 2003, is an interpretation of the Constitutional Court's law on the 1945 Constitution related to the examination of the Labor Law.